2011
DOI: 10.1016/j.ejvs.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The Scandinavian Propaten® Trial – 1-Year Patency of PTFE Vascular Prostheses with Heparin-Bonded Luminal Surfaces Compared to Ordinary Pure PTFE Vascular Prostheses – A Randomised Clinical Controlled Multi-centre Trial

Abstract: The Hb-PTFE graft significantly reduced the overall risk of primary graft failure by 37%. Risk reduction was 50% in femoro-poplitaeal bypass cases and in cases with critical ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 5 publications
1
39
1
Order By: Relevance
“…Expanded PTFE bonded with heparin (HePTFE) has been proposed as an alternative to autologous veins to reduce both early thrombotic risk and late myointimal hyperplasia development because of the anti-inflammatory properties of heparin. [27][28][29][30] Limited series have reported on HePTFE outcomes, but results are encouraging despite superiority of the GSV. One-year HePTFE patency rate ranged from 53% to 75%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanded PTFE bonded with heparin (HePTFE) has been proposed as an alternative to autologous veins to reduce both early thrombotic risk and late myointimal hyperplasia development because of the anti-inflammatory properties of heparin. [27][28][29][30] Limited series have reported on HePTFE outcomes, but results are encouraging despite superiority of the GSV. One-year HePTFE patency rate ranged from 53% to 75%.…”
Section: Discussionmentioning
confidence: 99%
“…One-year HePTFE patency rate ranged from 53% to 75%. [27][28][29][30] Neville et al, 29 in a comparison of tibial artery bypass performed with HePTFE and GSV to treat CLI, reported a 75% primary patency rate at 1 year and 81% limb salvage rate at 1 year despite 6.5% graft infection rate. Although reporting relatively short term, they suggested that these results do support HePTFE as a viable alternative conduit for patients with absent or poor-quality saphenous vein who need a tibial bypass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 These results cannot be extrapolated to hemodialysis access because of differences in the quality of flow and types of anastomosis in arterial bypass grafts. There is no published randomized trial concerning hemodialysis access grafts to compare with our study.…”
Section: Discussionmentioning
confidence: 94%
“…14 The introduction of the heparin-bonded technology has significantly improved patency rates of peripheral surgical bypasses. 15,16 Because endograft failure is often due to acute thrombosis rather than in-stent re-stenosis, the heparin-bonding technology has also been integrated with endografts. It is believed that the irreversible bonded heparin-molecules in the inner surface of the graft may prevent thrombosis, thus further increasing their performance.…”
mentioning
confidence: 99%